Customer Brand Engagement Generasi Milenial pada Produk Smartphone - Astra, Vitorio; Setiyaningrum, Ari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study aims to examine the effect of brand psychological ownership and value congruity on customer brand engagement, the effect of customer brand engagement on brand attachment and behavioral brand loyalty, and the mediating role of brand attachment on the effect of customer brand engagement on behavioral brand loyalty. The research model was tested on 232 millennial generation consumers who use Xiaomi brand smartphone products. The sampling method used purposive sampling technique and data analysis was carried out by SEM-PLS. The results of the study prove that customer brand engagement is influenced by value congruity and is not influenced by brand psychological ownership. Customer brand engagement was found to affect brand attachment and behavioral brand loyalty and brand attachment was found to affect behavioral brand loyalty. The results of the mediation test confirm that brand attachment mediates the effect of customer brand engagement on behavioral brand loyalty.